How the Second-Order Free Rider Problem Is Solved in a Small-Scale Society - Mathew, Sarah (American Economic Review, 2017)
Moralistic punishment enables human cooperation, but an outstanding question is why people voluntarily sanction when they can obtain the benefits of punishment without being enforcers themselves. To address how decentralized societies solve this second-order free rider issue, I examine why people punish among the Turkana, a population in Kenya in which informal peer sanctioning sustains participation in high-stakes interethnic warfare. Using vignette experiments I show that Turkana subjects express punitive sentiments toward second-order free riders and those who sanction irresponsibly. The prevalence of such meta norms regulating punishment reveal a possible pathway by which moralistic punishment could have evolved.